Analisa Kuantitas Dan Kualitas Airtanah Di Kabupaten Mojokerto - Pranowo, Harri; Sholichin, Moh.; Montarcih, Lily (Jurnal Teknik Pengairan: Journal of Water Resources Engineering, 2013)
Groundwater is one of the many alternative sources of water that has a large quantity and good quality. In the research area at Mojokerto regency, groundwater utilizing for irrigation but the use is limited, so it doesn’t cause environmental damage. This study aims to determine the quantity and quality of groundwater within the aquifer test, well test, and groundwater chemical test. For the aquifer test, this study use Long Period Test method to determine the type of flow between the steady state flow or unsteady state flow with the characteristics of confined aquifer, for well test in this research use step test method or step drawdown test method to determine the ability of wells production and the water quality test to determine the groundwater chemical characteristics with wilcox diagram and trilinier piper method with Aquachem 2011.1 demo version software. The results on the Mojokerto deep well (SDMJ) with an average depth of 100m - 120m including confined aquifer type, the existing discharge between 1.00 ltr / sec to 14.00 liters / sec, discharge potential between 2.33 ltr / sec to 33.07 liters / sec, optimum discharge between 3.90 ltr / sec to 19.80 liters / sec, for transmissivity values between 132.489 m 2 /day to 2047.140 m 2 /day, for the value of sea water intrusion (R) between 0.0727 meq / liter - 0.26027 meq / liter, on wilcox diagram the quality of water is in the (C2-S1) groups – with classification "Good" for agriculture. From the research result, the average quantity and the quality of groundwater wells pump is very good for agriculture.Keyword : Groundwater quality and quantity, aquifers, wells discharge, groundwater chemical, Aquachem version 2011.1 (demo version).